(untitled) (Bulletin KNOB, 2000)
The years between roughly the Munster Peace Treaty 1648 and the Year of Disaster 1672 was a period of great wealth and expansion for the Dutch Republic and particularly for Amsterdam, the ‘Golden Age’. In this period Amsterdam initiated large building projects and for the first time in its existence the town appointed a town architect, Daniel Stalpaert. This article sketches the Amsterdam town factory, i.e. the town building industry, chiefly during the third quarter of the 17th century. After a description of Daniel Stalpaert’s life, this article discusses the changing organization of the Amsterdam town factory in that period, followed by an account of the various functions within the town factory and the town architects and sub-architects working there. Attention is also paid to the town workplaces. The great changes within the town factory during the third quarter of the 17th century were caused by the enormous revival and decline of building activities and related to this the explosive growth and steady decrease of town architects, sub-architects and workmen. Structural changes saw to it that eventually the town architects were fully charged with policy, management and responsibility within the town factory, for which they were directly accountable to the town council. The town architect’s main task was to direct the two mega projects of that period: the building of the new town hall and the town expansion in 1662. Stalpaert was only briefly and partly in charge of the town factory. Daniel Stalpaert’s position within the town factory is therefore less prominent than assumed so far.